Performance of different management practices on tomato fruit borer (Helicoverpa armigera Hubner) abundance and infestation (Journal of the Bangladesh Agricultural University, 2017)
A research work based on eco-friendly management practices was undertaken at Agro-technology research field, Khulna University containing five treatments viz. Neem (Azadirachta indicia A. Juss.), Netting, Pheromone, Mahogoni (Swietenia mahagoni L.) and untreated control in RCBD with four replications aiming to evaluate their efficacy against tomato fruit borer, Helicoverpa armigera Hubner infestation. Data were taken on tomato fruit infestation (%), number of holes and number of larvae per infested fruit. All eco-friendly management practices had remarkable action against the tomato fruit borer, of which Netting claimed the highest position to protect tomato fruit borer infestation compared to other management practices whereas the highest insect infestation took place in untreated control. So, to infer, Netting is very promising and efficient tool in controlling tomato fruit borer for safe and quality tomato production.J. Bangladesh Agril. Univ. 14(2): 161-166, December 2016